Racial Capitalism and Difference: Structuring Exploitation and Expropriation of Resources through Differences in Nigeria - Miapyen, Buhari Shehu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Nigeria is a colonial creation and has diverse identities. These identities range from linguistic, ethnic, gender, class, spatial and religious forms. This thesis aims to analyze differences in Nigeria by drawing on the racial capitalism framework developed by Cedric Robinson. Differences in Nigeria are often analyzed by referring to class, ethnic divisions or civic/primordial dualism. Robinson made a novel contribution with his racial capitalism framework because he does not understand racialism in terms of differences in skin color but he explains racial capitalism as capitalism using differences (racial, gender or other forms of differences) to structure exploitation and expropriation of resources. The analysis conducted in this thesis is original because racial capitalism theories are often used to explain North American and Caribbean development yet they had not been used to explain African development in general and Nigeria in particular. This thesis will analyze racial capitalism in Nigeria by focusing on the recent history of differentiation and dispossession in the Niger-Delta region. It will engage itself with these questions: How are identities produced in the colonial period? How have these identities been reproduced in the subsequent post-colonial era in the Niger-Delta areas? How are these identities employed to structure exploitation of people and expropriation of resources to support capitalist accumulation? This thesis will also discuss land dispossession and pollution as dimensions of capitalist exploitation in the Niger Delta and examine the rise of community-based social movements in resistance to oil exploration and exploitation. Keywords: exploitation, expropriation, racial capitalism and difference

ÖZ: Nijerya kolonyal bir oluşumdur ve çeşitli kimliklere sahiptir. Bu kimlikler dilsel, etnik, cinsiyet, sınıf, mekansal ve dini biçimlere uzanır. Bu tez, Cedric Robinson tarafından geliştirilen ırksal kapitalizm çerçevesinden yararlanarak Nijerya'daki farklılıkları incelemeyi amaçlamaktadır. Nijerya'daki farklılıklar genellikle sınıf, etnik ayrımlar veya yurttaşlık / ilkel düalizmine atıfta bulunularak analiz edilir. Robinson, ırksal kapitalizm teorik çerçevesiyle yeni bir katkı yapmıştır çünkü ırkçılığı ten rengi farklılıkları olarak anlamlandırmamış ama ırksal kapitalizmi, kapitalizmin farklılıkları (ırksal, toplumsal cinsiyet ve diğer farklılıkları) kullanarak sömürüyü ve kaynaklara el koyulmasını yapılandırması olarak açıklamıştır. Bu tezde ortaya koyulan analiz özgündür çünkü ırksal kapitalizm teorileri genellikle Kuzey Amerika ve Karayipler'deki gelişmeyi açıklamak için kullanılır, ancak genel olarak Afrika'nın ve özel olarak Nijerya'nın gelişimini açıklamak için kullanılmamışlardır. Bu tez, Nijer Delta bölgesindeki farklılaşma ve mülksüzleştirmenin yakın tarihine odaklanarak Nijerya'daki ırksal kapitalizmi analiz edecektir. Bu tez şu sorulara yanıtlar bulmaya çalışacaktır. Sömürge döneminde kimlikler nasıl üretildi? Sömürge sonrası dönemde Nijer-Delta bölgelerinde bu kimlikler nasıl yeniden üretildi? Bu kimlikler, kapitalist birikimi desteklemek için insanların sömürülmesini ve kaynaklara el koyulmasını yapılandırmak için nasıl kullanılıyor? Bu tez aynı zamanda Nijer Deltası'nda kapitalist sömürünün boyutları olarak arazi mülksüzlüğünü ve kirliliği tartışacak ve petrol arama ve sömürüsüne direnişte toplum temelli toplumsal hareketlerin yükselişini inceleyecektir. Anahtar Kelimeler: sömürü, istimlak, ırksal kapitalizm ve farklılıklar
Doctor of Philosophy in International Relations. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2021. Supervisor: Asst. Prof. Dr. Umut Bozkurt.
Keywords: Political Science and International Relations; Nigeria--Politics and Government; Economic Conditions and Development--Nigeria; Racial capitalism--Nigeria; exploitation; expropriation; racial capitalism and difference